2014
DOI: 10.1093/cvr/cvu123
|View full text |Cite
|
Sign up to set email alerts
|

Impaired local regulation of ryanodine receptor type 2 by protein phosphatase 1 promotes atrial fibrillation

Abstract: PP1 regulates RyR2 locally by counteracting CaMKII phosphorylation of RyR2. Decreased local PP1 regulation of RyR2 contributes to RyR2 hyperactivity and promotes AF susceptibility. This represents a novel mechanism for subcellular modulation of calcium channels and may represent a potential drug target of AF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 58 publications
(55 citation statements)
references
References 39 publications
2
50
0
Order By: Relevance
“…In line with these current observations, a few recent studies also have shown the similar findings. 2, 3, 6 Further studies are needed to delineate the mechanisms underlying the differential responses in atria and ventricle.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In line with these current observations, a few recent studies also have shown the similar findings. 2, 3, 6 Further studies are needed to delineate the mechanisms underlying the differential responses in atria and ventricle.…”
Section: Discussionmentioning
confidence: 99%
“…18 1000μg of lysates was suspended with lysis buffer: 1% CHAPS in 1000μl RIPA buffer (pH 7.4) containing 150 mM NaCl, 10 mM Tis-HCl, 20 mM NaF, 1 mM NaVO 3 and protease and phosphatase inhibitor cocktails (cOmplete, Mini and PhosSTOP from Roche Applied Science, Indianapolis, IN). The samples were incubated at 4 °C with 3μl of RyR2 antibody (MA3-916; Thermo Scientific) or mouse IgG (M5284; Sigma) and rotated overnight.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[15] Since PP1 is believed to be primarily targeted to RyR2 via the R-subunit spinophilin ( Ppp1r9b ),[16] we studied the spinophilin knockout mouse and found a reduction in the association of PP1 with RyR2 by 70% while the global PP1 level was unchanged. [17] At the whole animal level, this disruption of PP1’s regulation of RyR2 also resulted in increased atrial ectopy and susceptibility to pacing-induced AF. [17] This study demonstrated for the first time that targeted disruption of PP1’s local regulation could have profound phenotypical consequences.…”
Section: Fundamental Challenge In Studying Pp1mentioning
confidence: 99%
“…Since protein phosphatases regulate RyR2 locally by counteracting CaMKII phosphorylation of RyR2 [29] and are a conserved serine/threonine phosphatase [30], we investigated the phosphorylation of PP1 and PP2A in cardiomyocytes under either high glucose or high [Zn 2+ ] i . As can be seen from Fig.…”
Section: Effect Of Increased [Zn 2+ ] I Level On Phosphorylation Levementioning
confidence: 99%